2016
DOI: 10.1111/jai.13041
|View full text |Cite
|
Sign up to set email alerts
|

Tocopherol, heavy metals (Cd, Pb, Cu, Fe, Mn, Zn), and fatty acid contents of thornback ray (Raja clavata Linnaeus, 1758) liver oil in relation to gender and origin in the Mediterranean and Black seas)

Abstract: Summary The study objective was to investigate the profiles of tocopherol, heavy metals, and fatty acids in the liver oil of female and male thornback ray Raja clavata from the Black and Mediterranean seas. The fish liver oil analyses were carried out by using a spectrophotometer (Hitachi U‐1900), ICP‐AES (Inductively Coupled Plasma‐Atomic Emission Spectrometry, and a GC‐MS (gas chromatography‐mass spectrometry), respectively. Results showed that the tocopherol content differed between the sample origin and ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 7 publications
0
4
1
Order By: Relevance
“…These values for liver oil of these two cartilaginous fish are lower than that of the liver oil of the average EPA+DHA levels obtained in this study. The mean EPA+DHA values in liver oil of males and females' R clavata were calculated to be 28.8% and 31.1% from Black sea and 28.2% to 30.6% from Mediterranean, respectively (Ozyilmaz 2016). These given values for liver oil of this cartilaginous fish for R clavata are higher than that of the liver oil of the average EPA+DHA levels obtained in this study.…”
Section: Figure 2 a Typical Fatty Acid Chromatogram Of Guitarfish Use...contrasting
confidence: 56%
See 2 more Smart Citations
“…These values for liver oil of these two cartilaginous fish are lower than that of the liver oil of the average EPA+DHA levels obtained in this study. The mean EPA+DHA values in liver oil of males and females' R clavata were calculated to be 28.8% and 31.1% from Black sea and 28.2% to 30.6% from Mediterranean, respectively (Ozyilmaz 2016). These given values for liver oil of this cartilaginous fish for R clavata are higher than that of the liver oil of the average EPA+DHA levels obtained in this study.…”
Section: Figure 2 a Typical Fatty Acid Chromatogram Of Guitarfish Use...contrasting
confidence: 56%
“…Fish oil are generally known to have higher amount of eicosapentaenoic acid (EPA, C20:5n3) and (DHA, C22:6n3). However, this fish liver oil surprisingly has got greatest amount of the C18:1n9+n7 comparing other cartilaginous fish species (Ozyilmaz 2016;Özyilmaz & Öksüz 2015;Ould El Kebir et al, 2007;Nechet et al, 2007). The C18:1n9+n7 is vulnarable to oxidize.…”
Section: Figure 2 a Typical Fatty Acid Chromatogram Of Guitarfish Use...mentioning
confidence: 85%
See 1 more Smart Citation
“…Similar levels with our study of EPA had been reported in liver oil of R. clavata. (Ozyilmaz, 2016). High proportions of DHA were detected in muscle and liver of Dasyatis marmorata (11.1% and 16.1%, respectively) caught from the East Tropical Atlantic Ocean (Ould El Kebir et al, 2003).…”
Section: Discussionmentioning
confidence: 92%
“…EPA and DHA represented 16-18% of the fatty acids present in the oil (Navarro-García et al, 2010). Unfortunately, available literature on liver oil studies from ray and shark species are limited in Turkish Seas (Tufan et al, 2013;Özyılmaz and Öksüz, 2015;Cabbar and Yığın, 2015;Özyılmaz, 2016). The aims of the present study explore the composition of liver oils derived from the thornback rays and smooth-hound.…”
Section: Introductionmentioning
confidence: 95%